2017
DOI: 10.1117/1.jnp.11.026015
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved investigation of competing nanocluster emission in quantum-disks-in-nanowires structure characterized by nanoscale cathodoluminescence

Abstract: Spatially resolved investigation of competing nanocluster emission in quantum-disks-innanowires structure characterized by nanoscale cathodoluminescence,"Abstract. We report on the study and characterization of nanoclusters-related recombination centers within quantum-disks-in-nanowires heterostructure by utilizing microphotoluminescence (μ-PL) and cathodoluminescence scanning transmission electron microscopy (CL-STEM). μ-PL measurement shows that the nanoclusters-related recombination center exhibits differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In our case, since we partially removed the Al-rich shell layer after passivation, the red-shift would be expected. We believe the subject of the red-shift mechanism after passivation is worthy of a separate detailed investigation, for example, by using nanoscale cathodoluminescence and TEM, as reported by Aditya et al…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In our case, since we partially removed the Al-rich shell layer after passivation, the red-shift would be expected. We believe the subject of the red-shift mechanism after passivation is worthy of a separate detailed investigation, for example, by using nanoscale cathodoluminescence and TEM, as reported by Aditya et al…”
Section: Resultsmentioning
confidence: 85%
“…17 In our case, since we partially removed Al-rich shell layer after passivation, the redshift would be expected. We believe the subject of the redshift mechanism after passivation is worthy of a separated detailed investigation, for example, by using nanoscale Cathodoluminescence and TEM, as reported by Aditya et al 24 There are various explanations for such PL emission enhancement after sample passivation. A flattened top surface of the nanowire indicated that we have possibly removed a portion (~5-10 nm) of the p-GaN layer.…”
Section: Methodsmentioning
confidence: 85%
“…The use of tightly focused electron beams allows for collecting spectral information directly from nanoscale samples with spatial resolution limited by the size of the focused electron beam. CL found applications in plasmonics, 7,[9][10][11][187][188][189][190][191][192][193][194] photonics, 195,196 semiconductors, [197][198][199] electron-beam lithography, 200 and tomographic reconstruction. 201 Additionally, the combination of spatial and spectral resolution can be combined to measure the dispersion of CL effects such as SPR.…”
Section: Cathodoluminescence Spectroscopy and Polarimetry Techniquesmentioning
confidence: 99%